Sustainability in the gig economy perspectives, challenges and opportunities in industry 4.0 - Gupta, Ashish; Tewary, Tavishi 1984-; Narayanan, Badri (Springer, 2022)
This book provides a comprehensive and contemporary source of reference for the gig economy for sustainable businesses with a focus on Industry 4.0. It covers the theoretical and practical implications of the rise of an alternative system in the era of technology-driven business entities; and explains the emergence of the gig economy as a crucial factor in devising approaches that will help in ensuring better decision making. As the COVID-19 pandemic rages on, investors and corporations are attempting to overcome the turbulence in financial markets over the past few months. Governments and economists are scrambling to mitigate the impacts of lockdowns. Many businesses have transferred to a remote working system, and the critical challenge remains to make this form of work and business productive, efficient, and sustainable. Against this backdrop, the book provides an overview of the gig economy from varied perspective such as general business and economics; ethics, governance, and legal issues; diffusion of IT in the workplace; sustainability; future of workforce and workplaces during and post-pandemic scenarios. This edited volume also highlights several challenges and opportunities for managing the diverse workforce in the prevailing situation which has no precedence. With its discussions on the impact of the gig economy on the business world, the book carries appeal for scholars in the business, human resource professionals, industry practitioners, corporates, and policy advocates interested in learning about evolution, automation, marketing, and sustainability in the gig economy